Construcción de un recurso lúdico computarizado, como apoyo al proceso de enseñanza aprendizaje de la asignatura de Inglés, para los niños de quinto grado paralelo B de la unidad educativa Lauro Damerval Ayora Nº1 de la ciudad de Loja, período 2015 - Ontaneda Abad, Andrea Genoveva (2016)
In the present research the researcher planted a recreational computerized resource, as a support of teaching-learning process in the subject of English to children of fifth grade parallel B at Lauro Damerval Ayora N°1 Educational Institution of the Loja city , 2015 period, based on the problematic found in teaching-learning process in the subjects’ skills and the lack of computerized teaching materials, the most difficult content were determined and applied through the interview and the survey applied and were included in the tool to strengthen them. To elaborate the application the researcher used the scientific and deductive methods, the first one final achieved the final product following each stage, the second one allowed the development of the theoretical framework, using the Cascada methodology the researcher obtained the users’ requirements, based on needs the activities were designed, then the investigator developed and codified the application, tests were performed to correct errors, she socialized and validated with the teacher and students with a validation card to measure the relevance and validity of the resource, giving positive results in the functional aspects, technical and pedagogical. Based on the results it might conclude that the use of recreational resource is a teaching tool, which improves the acquisition of learning in a fun and dynamic way to the student as an innovative strategy used by the teacher giving fulfillment to the new curriculum standards set by the Ministry of Education on the immersion of the information and communications technology in the classroom